2007
DOI: 10.1254/jphs.fmj06003x3
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms in the CNS and Peripheral Clock Disorders: The Circadian Clock and Hyperlipidemia

Abstract: Abstract. A circadian clock controls various physiological and behavioral rhythms. In mammals, a master circadian clock exists in the suprachiasmatic nucleus of the hypothalamus, and slave oscillators can be found in most tissues. These circadian oscillations are controlled by "clock genes". The negative feedback loop is thought to function as a molecular mechanism of the circadian clock. It is plausible that clock genes may control lipid metabolism through so-called clock-controlled genes and that lipid metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…22 Recent small community-based studies have also observed trends between short sleep duration, metabolic dysfunction and adiposity in children less than 10 years of age. 23,24 Mechanisms mediating the relation between inadequate or disturbed sleep, high cholesterol and weight gain include changes in the appetiteregulating hormones ghrelin and leptin, 25 preference for fatty foods 26 and circadian alterations in lipid metabolism. 26 In one study, the odds of obesity increased 5-fold for every hour reduction in sleep duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Recent small community-based studies have also observed trends between short sleep duration, metabolic dysfunction and adiposity in children less than 10 years of age. 23,24 Mechanisms mediating the relation between inadequate or disturbed sleep, high cholesterol and weight gain include changes in the appetiteregulating hormones ghrelin and leptin, 25 preference for fatty foods 26 and circadian alterations in lipid metabolism. 26 In one study, the odds of obesity increased 5-fold for every hour reduction in sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Mechanisms mediating the relation between inadequate or disturbed sleep, high cholesterol and weight gain include changes in the appetiteregulating hormones ghrelin and leptin, 25 preference for fatty foods 26 and circadian alterations in lipid metabolism. 26 In one study, the odds of obesity increased 5-fold for every hour reduction in sleep duration. 27 Similarly, Senegalese girls aged 13-14 years had a reduction in sleep of 6.85 minutes for every 1.0 increase in BMI.…”
Section: Discussionmentioning
confidence: 99%
“…This also means that a disrupted molecular circadian clock may underlie a wide-range of disorders and disease processes, including obesity, diabetes, and other components of the metabolic syndrome. Recent reviews have described detailed pathways by which the circadian clock may directly mediate lipid and glucose metabolism, as well as cardiovascular function [41,67,69,70]. Of particular interest are CCGs that contain binding sites in their promoter regions for core clock genes, which include albumin D-element binding protein (Dbp), orphan nuclear receptors (NRs) (i.e.…”
Section: Clock Controlled Genes and Clock-metabolic Gene Interplaymentioning
confidence: 99%
“…Melatonin (N-acetyl-5-methoxytryptamine), the principal secretory product of the pineal gland, produced during the dark phase of the circadian cycle, is a highly conserved antioxidant molecule [24,25] . Melatonin along with its metabolites has been shown to scavenge reactive oxygen species (ROS) or reactive nitrogen species (RNS) [26] .…”
Section: Introductionmentioning
confidence: 99%